SOCIAL ENGINEERING THROUGH SHARI’A: ISLAMIC LAW AND STATE-DIRECTED DA’WA IN CONTEMPORARY ACEH - Feener, R. Michael (UI Scholars Hub, 2013)
This study of the contemporary Islamic legal system in Aceh, Indonesia argues for new attention to be paid to the ways in which contemporary Muslim agendas for the implementation of Islamic law can be read as projects for future oriented social transformation—rather than as a series of reactive measures to perceived ‘crises of modernity’ and/or the political machinations of rival elites in contesting control of state power. In doing so it highlights the ways in which the ideals of, and institutional formations developed by, proponents of Islamic law are configured in relation to a broad range of non-Muslim modernist projects, including European and American theories of the sociology of law. rough examinations of these influences on discussions of Islamic law in Aceh, this essay demonstrates the degrees to which contemporary Sharī’a implementation is inextricably linked to broader configurations of law, moral authority, and state power in the modern global order.